Images of World and “Self”: Mechanism of Inclusion - A.A. Shestakov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The premises of cognition, the structures of living contemplation in particular, are considered in the paper. The relevance of the research is defined by the fact that the so-called paradigm of stimuli, which dominated in the gnosiological theory for a long time, proved to be increasingly insufficient for interpretation of cognition and its components sensual perceptual experience, natural language, and common sense. Accordingly, the research aims at consecutive investigation of the perceptual experience in cognitive activity and justification of the activity of cognitive process at the stage of sensory perception. The basic research method is the activity paradigm in the theory of cognition disclosing the dependence of the cognitive process on the image regulating it. This image carries out the function of incorporation of certain personal views into the system of universal values. The following conclusions are drawn from the obtained results: firstly, the cognitive act is initiated not by the effect of stimuli, but by putting forward the cognitive hypotheses; secondly, it is impossible to adequately comprehend the process of perception of the world by a person on the basis of strictly passive processing of sensory information, because this process relies on multi-parameter processes of reasoning, interpretation, and understanding; thirdly, the concept of empty space of subject-object relations, which is very popular in the reflexive philosophical tradition, is completely far from the reality composite social mechanics dominates here. The obtained results are important to become aware of the active nature of cognitive process, for studying the mechanisms for inclusion of the world image of a person (the structure of living contemplation) in their activity both practical and theoretical.